A sustainable approach for site selection of underground hydrogen storage facilities using fuzzy-delphi methodology - Nemati, Behrouz (2021)
One of the consequences of rapid global population growth is the increase in the energy demand. Currently, the main source of energy for various applications is fossil fuels, which are not renewable and their utilization at large scales have caused a number of environmental issues such as global warming. Hydrogen is one of the main renewable energy sources; however, its utilization has not yet been sufficiently commercialized due to some existing technical issues. For large-scale underground Hydrogen storage facilities, selecting the most suitable set-up location is accounted to be a crucial factor in order to use Hydrogen as a promising and environmentally friendly energy carrier. This study aims to develop an expert judgment approach for the prioritization of criteria involving site selection of large-scale Hydrogen storage facilities to support development of modern cities and industries. In this regard, Fuzzy-Delphi methodology was used to prioritize the criteria and sub-criteria, which seemed to be most relevant for the underground Hydrogen storage site selection process. A comprehensive screening was performed in the literature and eighteen criteria from technical, economic, health, safety and environment (HST) and social points of view were extracted. A professional questionnaire was designed for the criteria prioritization and SPSS 25.0 was employed to analyse the achieved results. According to the gained results, the most important sub-criteria were identified as legal restrictions, reservoir permeability and porosity, and regional risks. Also, the findings demonstrated that HSE and technical issues of sustainability for the site selection of H2 underground storage were more underscored in comparison to economic and social criteria. It is concluded that more in-depth studies are still needed to cover more aspects of sustainability regarding site selection for underground gas storages with special focus on social dimensions.